Adoption of Piezoelectric-enhanced Polyvinyl Alcohol/Polyvinylidene Fluoride Bilayer Composite Nanohydrogel in Bone and Cartilage Defect Repair in Rabbits - Xuan Sun; Shuai Wang; Honghui Tang; Haitao Yue; Feng Ji (Journal of Animal and Plant Sciences, 2025)
This study aimed to explore the therapeutic potential of piezoelectrically enhanced polyvinyl alcohol (PVA)/polyvinylidene fluoride (PVDF) bilayer composite nanohydrogel in bone and cartilage defect repair in rabbits.Employing silver nanowires (AgNWs) and nano-hydroxyapatite, a PVA/PVDF/AgNWs piezoelectric composite bilayer nanohydrogel was prepared and characterized through XRD, FTIR spectroscopy and electron microscopy. The piezoelectric, swelling, and mechanical properties of the nanohydrogel were evaluated. Rabbit bone marrow-derived mesenchymal stem cells (BMSCs) were divided into three groups: control, PVA/PVDF and PVA/PVDF/AgNWs groups. Cell viability was assessed via dual staining with acridine orange/propidium iodide (AM/PI) and visualized employing ImageJ. The expression of cartilage markers was measured by RT-PCR. A total of 30 rabbits with knee cartilage defects were divided into Group A (no intervention, blank control), Group B (intervention with PVA/PVDF hydrogel), and Group C (intervention with PVA/PVDF/AgNWs hydrogel), each with 10 rabbits.Gross observation and histological analysis were performed at eight weeks post-operation for cartilage repair evaluation.The PVA/PVDF/AgNWs piezoelectric composite bilayer nanohydrogel exhibited a three-dimensional network structure. The tensile fracture strength increased from 0.26 MPa to 0.6 MPa as the ethanol concentration increased. There was no significant difference in the proportion of live cells among the PVA/PVDF and PVA/PVDF/AgNWs groups and the control group (P>0.05). However, the expression levels of cartilage markers COL2A1, ACAN, and SOX9 were significantly higher in both experimental groups compared to the control group (P<0.05). In Group C, the defect site was almost completely covered by new cartilage, which showed significantly improved repair. Additionally, Group C exhibited significantly higher ICRS and histological scores than Groups A and B (P<0.05). The PVA/PVDF/AgNWs composite bilayer nanohydrogel exhibited low biotoxicity. It greatly enhanced chondrocyte growth and cartilage repair of rabbits, making it a valuable candidate in cartilage regeneration.
Keywords: polyvinyl alcohol; polyvinylidene fluoride; nanohydrogel; osteochondral defect; rabbit